Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1111/cid.12204
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Photodynamic Process (PDP) in Implant Osseointegration: A Histologic and Histometric Study in Dogs

Abstract: The use of photosensitivity drugs activated by LED demonstrated a tendency to stimulate bone formation, similar to autogenous bone graft on later time point.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 69 publications
(83 reference statements)
0
13
0
2
Order By: Relevance
“…When asked, if the therapy is used in promoting osseointegration [ Figure 8 ], (Sukumaran and Padavala, 2018), 69% of respondents were aware and 31% of respondents were unaware. According to (Faria, 2015) , they concluded that the use of photosensitisers by the therapy demonstrated a tendency to stimulate bone formation, similar to bone grafting.…”
Section: Resultsmentioning
confidence: 99%
“…When asked, if the therapy is used in promoting osseointegration [ Figure 8 ], (Sukumaran and Padavala, 2018), 69% of respondents were aware and 31% of respondents were unaware. According to (Faria, 2015) , they concluded that the use of photosensitisers by the therapy demonstrated a tendency to stimulate bone formation, similar to bone grafting.…”
Section: Resultsmentioning
confidence: 99%
“…Actually, proteinassociated liposomes (proteoliposomes) can be employed to investigate the action of photosensitive dyes applied during photodynamic therapy (Bolfarini et al 2012;Longo et al 2012;Faria et al 2015) to prevent/treat several diseases (Daghastanli et al 2004;De Lima Santos et al 2005;Zucolotto et al 2007;Ciancaglini et al 2012;Simão et al 2015). Proteoliposomes can be used to study how the protein-lipid interactions specifically affect the surface of the membrane model.…”
Section: Liposomes and Nanobiotechnologymentioning
confidence: 99%
“…Such systems can be used as biomimetic models for studies of interaction with various hydrophobic drugs and membrane proteins, with potential applications in the field of immunology (vaccines and drugs targeting specific cell membranes). Liposomes associated with proteins can be used to study the activity of photosensitive dyes applied during photodynamic therapy (Bolfarini et al 2012;Longo et al 2012;Rocha et al 2012;Bicalho et al 2013;Faria et al 2015), as well for studies related to the ability of proteins to prevent, treat and/or act as nanosensors for various diseases (Daghastanli et al 2004;Santos et al 2006;Zucolotto et al 2007;Migliaccio et al 2008;Colhone et al 2009Colhone et al , 2015Calderon et al 2009a, b;Perinoto et al 2010;Paulovich et al 2011;Barbosa et al 2011;Salay et al 2011;Barros et al 2013;Fotoran et al 2015).…”
Section: Liposomal Systems As Carriers For Bioactive Compoundsmentioning
confidence: 99%